The Influence of Islamic Religious Education Teacher Competence and Teaching Methods on Student Learning Achievement in Junior Secondary Schools - Diana Abdillah; Syahril; Ahmad Patih Ghozali (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Islamic Religious Education (PAI) in Indonesian junior secondary schools faces a persistent implementation gap between its philosophical centrality in character formation and the instructional realities of teacher capacity and pedagogical practice. This study examines the partial and simultaneous effects of PAI teacher competence and teaching methods on student learning achievement. Using a quantitative causal-explanatory design, data were collected from 157 students (20% of the school’s student population, selected through random sampling) at a state junior secondary school in Rembang Regency, Central Java, through structured questionnaires, supplemented by structured interviews with the school principal and PAI teachers. Data were analysed using multiple linear regression in SPSS, following validity testing (all items valid, r > 0.1567), reliability testing (Cronbach’s α > 0.94 for all variables), and classical assumption testing (normality, multicollinearity, and heteroscedasticity, all assumptions satisfied). Results show that teacher competence (X₁) has a significant positive partial effect on learning achievement (t = 3.442, β = 0.292, p = 0.001), and teaching methods (X₂) have a significantly stronger positive partial effect (t = 6.572, β = 0.558, p < 0.001). Simultaneously, both variables explain 67.1% of the variance in learning achievement (R² = 0.671; F = 157.244, p < 0.001). The substantially larger effect of teaching methods relative to teacher competence suggests that, within the constraints of this context, tactical pedagogical variation may exert a more immediate influence on observable academic outcomes than broader competency attainment, particularly under conditions of limited digital infrastructure. These findings underscore the need for pedagogically targeted teacher training and adequate instructional facility support in Islamic religious education.